Analisis Profesi Pengemis untuk Memenuhi Kebutuhan Pokok Perspektif Islam - Rahman, Holilur; Muhammadi, Hamas; Rohmah, Nafilatur; Mahfud, Moh. (Assyarikah: Journal of Islamic Economic Business, 2024)
This article aims to find out how Islam views the profession of begging with the aim of fulfilling basic needs. This research is a library research study using a descriptive analytical approach. The results of this research explain that begging behavior is not only caused by a person's inability to fulfill their basic needs (Hifdz an-Nafs), but is also caused by a desire to save or have wealth in a practical way. Therefore, in Islam the law makes begging as a profession either halal or haram, depending on the conditions and circumstances. However, Islam strictly prohibits its followers from begging except in emergency situations and forces its followers to work to meet their needs